Thermal Decomposition Mechanism and Kinetic Parameters of Semen Ziziphi Spinosae Based on Thermogravimetric Analysis - Fan, W.X.; Lu, X.F.; Meng, X.L.; Lan, Y.R.; Song, B.Z.; Ma, Q.L.; Chang, L.P. (Asian Journal of Chemistry, 2014)
Semen Ziziphi Spinosae, which was firstly recorded in "Shennong Bencao Jing", has long been used in traditional Chinese medicine. Large-scale cultivation and processing is the main direction of future development of Semen Ziziphi Spinosae. To improve the pharmacodynamics of Semen Ziziphi Spinosae, we must upgrade it by heating before using, but some thermosensitive materials contained in it can be changed in this process. The thermal decomposition and kinetics during continuous heating Semen Ziziphi Spinosae are the key factors. In this work, pyrolysis tests of Semen Ziziphi Spinosae were performed under non-isothermal TGA in order to determine its thermal degradation behavior. The kinetic parameters in this process were evaluated by using three different models, including iso-conversional models (KAS and FWO) and CR model. Good agreement with the experimental data from TGA test was observed for all models, especially CR model. The different calculating values of activation energy at different conversion between KAS model and FWO model implies the complexity and multi steps of Semen Ziziphi Spinosae pyrolysis.